PENGARUH MEDIA AUDIO-VISUAL DALAM PEMBELAJARAN BAHASA ARAB TERHADAP SISWA KELAS V DI MIS AL-HIDAYAH CK - Pratiwi, Ranti; Dian Kusuma Ningsih, Eka; Arfahmi, Khairunnisa (Penerbit Lafadz Jaya, 2022)
In an era that has increasingly sophisticated technology, a teacher must make the best use of it. So, the learning carried out in schools can be varied and interesting and fun to follow the learning process and not monotonous like that. That’s all from year to year, using audio media. Visual is one methode that can be used for learning process. So, students can enjoy learning during the learning process and can understand learning easily.